A Single‐Step‐Grown Semiconducting vdW Heterostructure of Tungsten Oxide–Sulfide for High‐Performance Photodetection. (3rd August 2022) - Chen, Guanyu; Hu, Xinyi; Gu, Mingwei; Wu, Hao; Chen, Keyu; Yu, Hao; Ren, Baiyu; Li, Zhong; Luan, Yange; Tang, Tao; Cheng, Yinfen; Huang, Haibo; et al.
Abstract: Ultrathin semiconducting van der Waals (vdW) heterostructures based on transition metal dichalcogenides (TMDs) play a critical role in developing next‐generation electronic and optoelectronic devices. The replacement of one component of the heterostructure by transition metal oxides (TMOs) certainly brings in numerous benefits including long‐term stability and novel functionalities. However, the single‐step chemical‐vapor deposition growth of TMOs/TMDs vdW heterostructures, as a highly desired approach for large‐scale fabrication and practical implementation, is challenging due to contradictory growth atmospheres of TMOs and TMDs. Here, the single‐step growth of an ultrathin WO3–x /WS2 vdW heterostructure based on the quantity‐driven discrepant interaction between S and the precursor, in which S induces sulfidation to produce WS2 in the S‐rich phase and is changed to the reduction role to obtain sub‐stoichiometric WO3–x in the S‐deficient phase is realized. Both WO3–x and WS2 exhibit semiconducting properties with a favorable type‐II band alignment. A wide response across the entire visible spectrum with a large photo‐responsivity of 4375 A W −1, a detectivity of 5.47 × 10 11 Jones, and sub‐ms switching kinetics at 405 nm is achieved without gating bias, which is significantly improved over other reported ultrathin vdW heterostructures. This study demonstrates the possibility of single‐step‐growing TMOs/TMDs vdW heterostructures and their strong potential in high‐performance optoelectronic devices. Abstract : Ultrathin vdW heterostructure of WO3‐x /WS2 is constructed in a facile one‐step manner. The heterostructure demonstrates an ultrahigh photo‐responsivity and detectivity with a remarkable high‐speed switching due to its Type‐II band alignment. This study presents a facile and highly controllable approach to synthesize ultrathin TMOs/TMDs vdW heterostructures with strong potential in high‐performance photodetection applications.